Enhancement of reactive oxygen species formation in stable and unstable asthmatic patients - Vachier, I; Chanez, P; Le Doucen, C; Damon, M; Descomps, B; Godard, P (The European respiratory journal, 1994)
There is increasing evidence to suggest that human blood polymorphonuclear neutrophils (PMNs) and monocytes play an important role in the inflammatory processes of asthma. In asthmatic patients, PMNs and monocytes were shown to be activated more than in healthy subjects. We investigated the capacity of these two cell populations to generate reactive oxygen species (ROS) in stable and unstable asthmatic patients. The two populations of asthmatic patients were identified by asthma activity, as expressed by clinical events occurring within 2 weeks prior to the study. Oxygen species formation was analysed for isolated purified PMNs and monocytes (Mos) by chemiluminescence (CL) using lucigenin and luminol as luminescent probes. CL was determined on nonstimulated and on phorbol myristate acetate (PMA)-stimulated cells. The stimulatability coefficient (PMA-stimulated/nonstimulated cell ratio) of each cell population was then calculated. Resting PMNs and Mos generated significantly greater amounts of ROS in stable asthmatic patients, and much more in unstable asthmatic patients, as compared to healthy subjects, both in lucigenin and luminol enhanced CL. Non O2.- ROS production from PMA-stimulated PMNs and Mos was identical in unstable asthmatic patients and in healthy subjects, whereas a significant decrease was observed in stable asthmatic patients, as assessed by luminol enhanced CL. PMA-stimulated cells showed no difference in O2.- generation, as assessed by lucigenin enhanced CL. However, the stimulatability coefficient of all asthmatic patients was always significantly lower than that of healthy subjects. These results suggest that there are differences in priming and stimulation of Ros production from PMNs and Mos between stable and unstable asthmatic patients.